RETROSPECTIVE ASSESSMENT OF JOINT SYNDROME AND JOINT STRUCTURE DISORDERS IN OSTEOARTHRITIS - Khalmurad Akhmedov, Sagdiyana Buranova, Ikhtiyor Turaev (Galaxy International Interdisciplinary Research Journal, 2023)
The purpose of the study: Retrospective assessment of clinical signs and course of the disease in patients with osteoarthritis in the ratio of gender.This research study conducted a retrospective analysis of 300 patients hospitalized at the City Clinical Hospital No.3 from 2015 to 2019 on the basis of medical records and emphasized the analysis of the clinical course and consequences of the disease. On the basis of the obtained documents, the joint syndrome and disorders of the joint structure observed in patients with osteoarthritis (OA) were assessed by radiological images. It was noted that in patients with OA, joint syndrome was different and gender differences were identified.